Violence and Political Advocacy in the Lost Counties, Western Uganda, 1930-64 - Peterson, Derek R. (The International journal of African historical studies, 2015)
There were, of course, other populisms from which Obote might have drawn: in Zanzibar, an army claiming to represent the interests of commoners had overthrown the centuries-old government of the Sultan; in Rwanda, a majoritarian party had overthrown Rwanda's king.96 But no other populist political theory was so available, so fully documented in Obote's own archives, or so carefully attended to. The logic of Nyoro activism-the contrast between the popular will and the narrow self-interest of the Ganda ruling class; the claim that a self-governing African state should blot out inherited inequalities; the condemnations of feudalist tyranny- became the guiding logic of Ugandan socialism, and a rationale for a one-party dictatorship.